The diffused religious choice when applying for a university degree in Sydney. Issue 1 (2nd January 2023) - Possamai, Adam; Possamai-Inesedy, Alphia; Piracha, Awais
ABSTRACT: While the preference for university by school leavers has been researched extensively, this article seeks to explore if religious influence might also come to play when selecting a university, with particular reference to Australia, a country whose higher education environment is largely made up of public, secular universities. The data used is the first preference that students in High Schools in NSW make for an urban and public university in Sydnney, and is analysed statistically and with social mapping tools. While this article cannot prove a direct religious choice when it comes to a university, it nevertheless shows some patterns in Sydney that cannot be ignored. There is an influence of religion through various geographical patterns and socio-economic factors that have been affected by religions over the history of Sydney. Using the theory on Diffused Religion by Roberto Cipriani, this article concludes that there is indeed a religious choice, but diffused, from someone who has attended a high school and choose a university, be it consciously religious or not.